Endoscope-Assisted Excision of a Juxtafacet Cyst in an Adolescent Athlete: A Case Report - Hopkins, Justin; Sakai, Toshinori; Sairyo, Koichi; Mefford, Jason; Bhatia, Nitin N.; Tonogai, Ichiro; Dezawa, Akira; Yasui, Natsuo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Juxtafacet cysts (JFCs) are a cause of back and radicular pain that can be treated conservatively and operatively. Such strategies include lumbosacral brace, epidural injection, open surgery, and minimally invasive surgery; although surgical treatment is usually reserved for unsuccessful conservative treatment. The role of minimally invasive surgery in athletic youth with JFCs has yet to be determined.Patients/Material and Methods The patient is a 16-year-old basketball player with a JFC. We performed endoscope-assisted cystectomy.Results Endoscope-assisted JFC excision immediately and completely resolved the patient's lower back and leg pain with no recurrence of symptoms 4 years after surgery.Conclusion We suggest that JFCs of the lumbar spine be a part of the differential diagnosis in young patients with back and radicular pain. Furthermore, we recommend that endoscope-assisted surgery be employed in the treatment of JFCs in young athletes.
Keywords: adolescent; athlete; endoscope; juxtafacet cyst; lumbar spine